2022
DOI: 10.1186/s40168-022-01287-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced chemodiversity suppresses rhizosphere microbiome functioning in the mono-cropped agroecosystems

Abstract: Background Rhizodeposits regulate rhizosphere interactions, processes, nutrient and energy flow, and plant-microbe communication and thus play a vital role in maintaining soil and plant health. However, it remains unclear whether and how alteration in belowground carbon allocation and chemodiversity of rhizodeposits influences microbiome functioning in the rhizosphere ecosystems. To address this research gap, we investigated the relationship of rhizosphere carbon allocation and chemodiversity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 72 publications
2
28
1
Order By: Relevance
“…Although reported that pH and EC played the most significant role in shaping bacterial communities. However, in current study, pH and EC presented no significant correlation with all phyla in non-rhizosphere sediments and significant correlation with several phyla in rhizosphere sediments, which might explain the positive association of oxygen regulation by bacterial communities (Huang et al, 2020) and root exudates (Lv et al, 2020).…”
Section: Links Between Sediment Bacterial Communities and Environment...contrasting
confidence: 69%
See 1 more Smart Citation
“…Although reported that pH and EC played the most significant role in shaping bacterial communities. However, in current study, pH and EC presented no significant correlation with all phyla in non-rhizosphere sediments and significant correlation with several phyla in rhizosphere sediments, which might explain the positive association of oxygen regulation by bacterial communities (Huang et al, 2020) and root exudates (Lv et al, 2020).…”
Section: Links Between Sediment Bacterial Communities and Environment...contrasting
confidence: 69%
“…Aquatic plants, as an important part of the lake ecosystem, also play an important role in the fate of pollutants in lakes ( Zhang et al, 2022 ). Rhizosphere sediment regulates rhizosphere interactions, processes, antibiotics migration and transformation and thus play a vital role in maintaining plant health and ecosystem stability ( Li et al, 2022 ). However, rhizosphere bacterial community also received much attention due to their associations with plant growth and pollution in lake ecosystems ( Marschner et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…17 Ramlibacter, as a PGPR, is capable of not only N fixation, N degradation and assimilatory nitrate reduction, thus promoting the accumulation of ammonium in soil ecosystem, 59 but also inhibiting pathogens and in turn increasing plant disease resistance. 60 Similarly, Saccharimonadales was found to be the dominant bacteria in salt stress and synergistically influenced the abundance soil nitrogen cycling-related genes. 61 Hydrogenophaga could not only act as denitrifying species and bacteria degrading organic substances to improve soil nutrient (e.g., C, N, P) turnover and cycling 62 but also acts as a PGPR, upregulating several functional enzymes in soybean plants such as carbonic anhydrases (related to photosynthesis), asparagine synthetase 2 (related to asparagine synthesis), and glutathione S-transferase (related to antioxidant processes), thus increasing soybean plant growth and resistance under salt stress conditions.…”
Section: Effect Of Si Qds On Radish Rhizosphere Microbial Communitymentioning
confidence: 97%
“…Plant-associated microorganisms play a major role in affecting plant growth and health (Muller et al, 2016 ; Theis et al, 2016 ; Singh et al, 2020 ; Woodhams et al, 2020 ). The rhizosphere, a hot spot for plants to exchange substances and energy with the surrounding environment, has drawn the most attention (Li et al, 2020 ; Li P. et al, 2022 ). There is an emerging consensus about the dominant role of the rhizosphere microbiome in influencing host performance, especially regarding resistance to disease (Berendsen et al, 2012 ; Li X. et al, 2019 ); for example, disrupting the balance between the abundances of Firmicutes and Actinobacteria in the tomato rhizosphere causes increased incidence of bacterial wilt disease (BWD; Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%